Upaya Peningkatan Mutu Pendidikan Agama Islam: Problematika dan Solusi - Jadidah, Amatul (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2021)
Education is a means in building the character of the nation in building a highly civilized society, where Islamic Religious Education is an important part.. For this reason, efforts to improve the quality of religious education are important to overcome the problems. The purpose of this study was to find out the problems of implementing Islamic religious education and how to improve the quality of education at Madrasah Ibtidaiyah Al Hikmah in Wringinanom, Poncokusumo District, Malang Regency. In this study, the researcher uses a qualitative type, which emphasizes natural descriptions, and data collection or phenomena collection is carried out from reasonable circumstances. Therefore, researchers are directly involved in the field. From the results of the study, there were several problems found, namely: low cognitive abilities of students; commitment, quality and competence of educators that need to be improved; The lack of understanding of educators about the 2013 curriculum; lack of cooperation between a small number of parents and educators and limited infrastructure. Efforts to overcome these problems, madrasas are carried out in several ways: for students, providing educational sanctions, forming student group work, discussions between students in class, and providing additional hours. For educators, participating in seminars and workshops. For the curriculum, by increasing the socialization of the implementation of the 2013 curriculum. For management, it seeks to increase the involvement between the guardians of students and the community in an effort to improve quality, through meetings. For facilities and infrastructure, the school will seek the realization of facilities and infrastructure that do not yet exist, such as libraries.